Resistance acquired to third generation tyrosine kinase inhibitors in non small cell lung cancer - Runciman Gozzer, Thanya (2018)
Resistance to third-generation tyrosine kinase inhibitors (TKI) is an increasingly frequent event in clinical practice; however, the exact mechanisms by which tumor cells develop such resistance allowing their survival are unknown. A case of resistance to osimertinib (AZD9291) in non small cell lung cancer, evidenced by next generation sequencing (NGS) and its possible therapeutic approach is described.